Serial Frequencies and Clinical Features of Uveitis in Hokkaido, Japan. (24th August 2017) - Iwata, Daiju; Mizuuchi, Kazuomi; Aoki, Koki; Horie, Yukihiro; Kase, Satoru; Namba, Kenichi; Ohno, Shigeaki; Ishida, Susumu; Kitaichi, Nobuyoshi
ABSTRACT: Purpose : Environmental and lifestyle changes influence the clinical features of uveitis. This study reviewed the epidemiologic trends of uveitis in the Japanese population. Methods : A retrospective review of the past 80 years of reports from Hokkaido University Hospital. Results : In the 1930s, tuberculosis accounted for 46% and syphilitic uveitis for 31% of cases. The frequency of these diseases decreased to 12% in the 1950s; 8% in 1969; 0.6% in the 1990s; and 0.8% in the 2000s, while the rate of non-infectious uveitis increased. The three most common specific diagnoses were: sarcoidosis, Vogt–Koyanagi–Harada disease, and Behçet disease. Although Behçet disease was the most frequent non-infectious uveitis until the 1980s, sarcoidosis is now the most frequent cause of newly diagnosed non-infectious uveitis. Conclusions : The etiology of uveitis has changed with the times. Tubercular and syphilitic cases have greatly decreased, and sarcoidosis is the most frequent type of uveitis today.